Training cognitive flexibility in patients with anorexia nervosa: A pilot randomized controlled trial of cognitive remediation therapy. Issue 1 (28th October 2013) - Brockmeyer, Timo; Ingenerf, Katrin; Walther, Stephan; Wild, Beate; Hartmann, Mechthild; Herzog, Wolfgang; Bents, Hinrich; Friederich, Hans‐Christoph
ABSTRACT Objective Inefficient cognitive flexibility is considered a neurocognitive trait marker involved in the development and maintenance of anorexia nervosa (AN). Cognitive Remediation Therapy (CRT) is a specific treatment targeting this cognitive style. The aim of this study was to investigate the feasibility and efficacy (by estimating the effect size) of specifically tailored CRT for AN, compared to non‐specific cognitive training. Method A prospective, randomized controlled, superiority pilot trial was conducted. Forty women with AN receiving treatment as usual (TAU) were randomized to receive either CRT or non‐specific neurocognitive therapy (NNT) as an add‐on. Both conditions comprised 30 sessions of computer‐assisted (21 sessions) and face‐to‐face (9 sessions) training over a 3‐week period. CRT focused specifically on cognitive flexibility. NNT was comprised of tasks designed to improve attention and memory. The primary outcome was performance on a neuropsychological post‐treatment assessment of cognitive set‐shifting. Results Data available from 25 treatment completers were analyzed. Participants in the CRT condition outperformed participants in the NNT condition in cognitive set‐shifting at the end of the treatment (p = 0.027; between‐groups effect size d = 0.62). Participants in both conditions showed high treatment acceptance. Discussion This study confirms the feasibility of CRT for AN, and provides a first estimate of the effect size that can be achieved using CRT for AN. Furthermore, the present findings corroborate that neurocognitive training for AN should be tailored to the specific cognitive inefficiencies of this patient group. © 2013 Wiley Periodicals, Inc. (Int J Eat Disord 2014; 47:24–31)